The Clinico-epidemiologic Characteristics of Iraqi Patients with Neuroendocrine Tumors and Their Response to Long Acting Octreotide - Abdulfattah, Marwah K.; Al-naqqash, Manwer A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: The lack of studies regarding the neuroendocrine tumors (NET) is related to the rarity of these tumors .Long acting Octreotide is an established treatment for NETs by both providing symptomatic relief & inhibiting tumor growth. However, studies regarding incidence of NETs & their response to long acting Octreotide are still insufficient. Objectives: To study the clinico-pathologic characteristics of Iraqi patients with NET & their response to long acting Octreotide. Patients & methods: This is a cross-sectional observational study that was conducted in Oncology teaching hospital using patients’ follow-up records. Data recruitment included all NET patients diagnosed after October 2013. Results: During the study period (2 years) ,38 patients were recorded in Iraq/oncology teaching hospital NET Registry. Patients ` data (age, gender, site of the tumor, metastatic status as well as type of therapy applied) were collected. Twenty one (55.3 %)of the patients were males, M:F=1.2:1 , while 23 patients (60.5%) were over the age of 50 years .The gastroenteropancreatic (GEP) tract being the most common primary site followed by pelvis We found metastatic disease at presentation in 17 (44.7% ) of patients and the Liver was the most common metastatic site found in (15.8%, 6 patients). Seventeen (44.7%) patients presented with Grade 3 . Most common therapy applied in our patients included systemic chemotherapy, surgery, long acting Sandostatin & radiotherapy for palliation only according to both NCCN & ESMO guidelines. The median time of remission following Somatostatin analogue (SSA) administration was 3 months compared to 7 months in patients received other modalities of treatment (p=0.003). Conclusion: Octreotide LAR provides symptomatic response & contributes to disease stabilization & tumor regression in both functional & non functional NETs.